2021
DOI: 10.1093/schbul/sbaa183
|View full text |Cite
|
Sign up to set email alerts
|

Timing, Distribution, and Relationship Between Nonpsychotic and Subthreshold Psychotic Symptoms Prior to Emergence of a First Episode of Psychosis

Abstract: Prospective population studies suggest that psychotic syndromes may be an emergent phenomenon—a function of severity and complexity of more common mental health presentations and their nonpsychotic symptoms. Examining the relationship between nonpsychotic and subthreshold psychotic symptoms in individuals who later developed the ultimate outcome of interest, a first episode of psychosis (FEP), could provide valuable data to support or refute this conceptualization of how psychosis develops. We therefore conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Although the incidence of PE-only was not clinically neutral – as evidenced by some degree of association with most of the 17 factors under examination, these associations were (significantly) weaker as compared to PE + NPD and there was no association with health care use. These results concur with the previously documented suggestion that clinically relevant psychosis is an indicator of severity in the constellation with non-psychotic psychopathology, and should not be considered in isolation (van Os and Reininghaus, 2016 ; van Os and Guloksuz, 2017 ; Cupo et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the incidence of PE-only was not clinically neutral – as evidenced by some degree of association with most of the 17 factors under examination, these associations were (significantly) weaker as compared to PE + NPD and there was no association with health care use. These results concur with the previously documented suggestion that clinically relevant psychosis is an indicator of severity in the constellation with non-psychotic psychopathology, and should not be considered in isolation (van Os and Reininghaus, 2016 ; van Os and Guloksuz, 2017 ; Cupo et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, our evidence supports further investigation, in prospective CHR-P settings, of the hypothesis that non-psychotic psychopathology represents a necessary factor in the ontogenesis of psychotic disorders, such that the pathway from psychosis risk to clinical psychosis outcome requires a non-psychotic intermediary state, interacting with multiple conditions including cognitive alteration, high PRS-SZ and environmental exposure. Indeed, a recent follow-back study of a representative incidence sample confirmed this supposition (Cupo et al ., 2021 ). Therefore, CHR-P/APS research should be reconceptualised from a focus on attenuated psychotic symptoms with exclusion of DSM-disorders, as the ‘pure' representation of a supposedly homotypic psychosis risk state, towards a focus on poor-outcome NPDs, characterised by a degree of psychosis admixture, on the pathway to psychotic disorder outcomes (van Os and Reininghaus, 2016 ; Guloksuz et al ., 2020 ; Cupo et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Onset of psychosis is characterized by presence of active psychotic symptoms and occurs during early adulthood. Psychosis onset is also better understood as a continuum with psychosis patients reporting proportionally more nonpsychotic symptoms (such as depression and anxiety among others) prior to the onset of psychosis [22]. As symptoms segregate with growth and development psychopathology symptom relationships potentially become statistically more independent.…”
Section: Parameter Estimatesmentioning
confidence: 99%